The Virtual Puget Sound - A Process to Evaluate Alternative Futures for Puget Sound? - Richey, Jeffrey E. (University of Washington Water Center, 2008)
Richey will present Puget Sound Regional Synthesis Model (PRISM). The model includes feedbacks between biophysical processes and impacts, environmental stressors, and urban processes in the Puget Sound. Richey will describe the key communication goals, including organizing and processing information and decision needs, collaboration between specialists, and reaching the citizens of Puget Sound. He will outline the structure of the project, using example studies to illustrate the features and capabilities.
Keywords: environmental models; hydrologic models; information dissemination; Washington; estuaries; climate; surface water; runoff; watersheds; stream flow; rivers